Chapter 16 Afterword - Franklin, Sophie (Taylor & Francis, 2024)
Building upon Sudeshna Chatterjee's concluding chapter in this volume and its reflections upon who is and is not included in social contracts of consent, the Afterword reflects on how an intersectional approach to consent can help coordinate calls to defund and abolish the police. Exploring connections between racist violence and institutional misogyny in the US and UK police forces respectively, the Afterword examines how the concept of ‘policing by consent’ is a discriminatory one that does not offer the opportunity for individuals to withdraw their consent. In bringing together intersectional approaches to protesting racist and misogynistic violence, the Afterword puts forth new ideas for the relevance of consent in debates about policing, protest, and healthcare equity, while reflecting on the approaches adopted in this volume and their potential for future research.